Vegetarianism in Food-Based Dietary Guidelines - Baroni, Luciana (International Journal of Nutrition, 2015)
Plant foods are staples of many cultures in the world. Conversely, the appearance of vegetarianism in Western countries is a relatively recent phenomenon, showing an upward trend: people following vegetarian diets (both lacto-ovo-vegetarian-LOV and vegan-VEG), account today for about 10% of the Western population. According to the principle of non-discrimination, the most recent national dietary guidelines for the general population (DGLs) of some Western countries have adapted their contents to comprise vegetarian eating patterns. Moreover, since 1997, specific vegetarian food guidelines (VFGs) were developed. The aim of this review was to summarize and compare the information and recommendations of the food-based dietary guidelines (FBDGs) contained in the DGLs usable by vegetarians, and in the main VFGs; to extract a list of basic criteria for the planning of a well-balanced vegetarian diet, and to identify the most valid FBDG for vegetarians. An Internet search was conducted in the English language, in order to identify national DGLs applicable to vegetarian dietary patterns, and international VFGs. Four Western DGLs and six VFGs were selected. Compared to the majority of DGLs, VFGs are not an "adaptation" of omnivorous (OMN) eating patterns to vegetarian ones, but rather devoted guides: they include only foods consumed by vegetarians, and take into account their specific nutritional needs. VFGs offer qualified advice to meet the most updated standards of adequacy and safety of the diet: the varied consumption of all plant foods, mainly unprocessed; the respect of individual’s calorie requirements; the optional addition of small amounts of foods of animal origin (dairy/eggs); the attention towards some potentially critical nutrients. According to this criteria, the VFG for North American Vegetarians can represent the most accurate and practical model: not only is it consistent with research on the adequacy of vegetarian diets, but it is applicable both to LOV and VEG eating patterns and to all lifecycle stages beyond 4 years of age.
Keywords: vegetarian nutrition; plant food; dietary guidelines; vegetarian food guides.